High-Frequensy Short-Pulsed Metal Plasma-Immersion Ion Implantion Or Deposition Using Filtered DC Vacuum-ARC Plasma; Surface and Coatings Technology; Vol. 201, № 15 - Ryabchikov A. I. Aleksandr Ilyich; Ryabchikov I. A.; Stepanov I. B.; Usov Y. P. Yuri Petrovich (2007, 2007)
A new approach to the development of advanced coating deposition and ion implantation method including an application of filtered dc metal plasma and high-frequency short-pulsed negative bias voltage with a duty factor in the range of 10-99% are considered. The ion energy spectrum for different negative bias potential pulse durations (120-1100ns) was measured. The chart of various methods of ion beam and plasma material treatment using high-frequency short pulse metal plasma immersion ion implantation or deposition depending on bias pulse duty factor and amplitude for Cu plasma is presented. The ion assisted coating deposition has been examined depending on samples conductivity and thickness, plasma concentration, pulse repetition rate, amplitude, and duty factor.